PI3K-AKT-mediated phosphorylation of Thr260 in CgCaspase-3/6/7 regulates heat-induced activation in oysters - Chaogang Wang; Mingyang Du; Zhuxiang Jiang; Rihao Cong; Wei Wang; Taiping Zhang; Jincheng Chen; Guofan Zhang; Li Li (Communications Biology)
Abstract Cysteine-aspartic proteases (caspases) are critical drivers of apoptosis, exhibiting expansion and domain shuffling in mollusks. However, the functions and regulatory mechanisms of these caspases remain unclear. In this study, we identified a group of Caspase-3/6/7 in Bivalvia and Gastropoda with a long inter-subunit linker (IL) that inhibits cleavage activation. Within this region, we found that conserved phosphorylation at Thr260 in oysters, mediated by the PI3K-AKT pathway, suppresses heat-induced activation. This mechanism is involved in divergent temperature adaptation between two allopatric congeneric oyster species, the relatively cold-adapted Crassostrea gigas and warm-adapted Crassostrea angulata. Our study elucidates the role of these effector caspase members and their long IL in bivalves, revealing that the PI3K-AKT pathway phosphorylates Thr260 on CgCASP3/6/7’s linker to inhibit heat-induced activation. These findings provide insights into the evolution and function of apoptotic regulatory mechanisms in bivalves.